Does the tumour microenvironment alter tumorigenesis and clinical response in transmissible venereal tumour in dogs? - Ballestero Fêo, H. [UNESP]; Montoya Flórez, L. [UNESP]; Yamatogi, R. S.; Prado Duzanski, A. [UNESP]; Araújo, J. P. [UNESP]; Oliveira, R. A. [UNESP]; Rocha, N. S. [UNESP] (Wiley, 2018)
The canine transmissible venereal tumour (CTVT) is a transmissible cancer that is spread naturally between dogs, with the ability to develop and evade the immune system, despite strict immune surveillance of the host. Furthermore, molecular signalling between cells of the immune system and the tumour microenvironment appear to influence the behaviour and development of the tumour. Thus, this study aimed to quantify the expression of genes related to the immune system such as IL-6, IFN-γ, and TGF-β, as well as angiogenic factors (VEGF, CXCR4), in CTVT cells in vivo and in vitro (primary culture), correlating with the clinical response of the animals treated with vincristine. As expected, the most prevalent subtype was plasmacytoid cells, although lymphocytic cells were also found, indicating the possibility of polyclonality. When we compared the gene expressions of IFN-γ and IL-6, we mostly found low expression, concluding that MHC expression was probably not occurring in tumour cells, and no activation of immune cells to eliminate the tumour. The TGF-β gene was normal in the majority of animals but demonstrated decreased expression in vincristine resistant animals, leading to the hypothesis that the concentration of tumour-derived TGF-β was affecting and even suppressing the real TGF-β expression, favouring tumour proliferation and progression in these cases. VEGF expression was extremely high, demonstrating its angiogenic role in tumour growth, while CXCR4 was decreased, possibly because of CTVT’s low metastatic potential. Thus, we concluded that the tumour microenvironment, together with the immune system of the host, influences CTVT, presumably altering its tumorigenesis and the animal’s clinical response to treatment.
Keywords: cancer; CTVT; dog; tumour microenvironment